SPELLBOUND BY SOUNDTRACKS. AN INTERVIEW WITH FILM SCORE COMPOSER AARON FAZAKAS - Adél FEKETE (Studia Universitatis Babeş-Bolyai. Musica)
In the following interview we tried to introduce the reader into the artistic world of a 21st century composer. We sat down with composer Aaron Fazakas to talk about inspiration, film score composing, the relationship between the audio and visual realms of a movie, and the meaning of art in his view. As the PhD student of Ede Terényi, one of the great contemporary Transylvanian composers, Aaron Fazakas revealed his own artistic creed, the reasons for which he composes and the relationship he has with his audience, while also discussing his work as a teacher, molding the minds of future generations of artists.